1997
DOI: 10.1037/0096-1523.23.4.1153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of background knowledge on object categorization and part detection.

Abstract: Previous research has shown that background knowledge affects the ease of concept learning, but little research has examined its effects on speeded categorization of instances after the category is well learned. Subjects in 4 experiments first learned novel categories. At test, they categorized a new set of novel stimuli that were either consistent or inconsistent with background knowledge given about the categories. Background knowledge affected categorization responses in an untimed task, with usual reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
81
0
7

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 44 publications
9
81
0
7
Order By: Relevance
“…Similarity and distance knowledge could develop within about a second per string (as the above chance similarity and distance knowledge in the time pressure inconsistent condition suggests). This finding is broadly consistent with categorization research showing that general knowledge can be applied early on during categorization (e.g., Lin & Murphy, 1997;Luhmann et al, 2006;Palmeri & Blalock, 2000).…”
Section: Learning Under Time Pressure and Dual Task Conditionssupporting
confidence: 89%
See 1 more Smart Citation
“…Similarity and distance knowledge could develop within about a second per string (as the above chance similarity and distance knowledge in the time pressure inconsistent condition suggests). This finding is broadly consistent with categorization research showing that general knowledge can be applied early on during categorization (e.g., Lin & Murphy, 1997;Luhmann et al, 2006;Palmeri & Blalock, 2000).…”
Section: Learning Under Time Pressure and Dual Task Conditionssupporting
confidence: 89%
“…This condition allows us to distinguish between performance factors that require time to develop and ones that do not. For example, perceptual categorization research has shown that the application of background knowledge can be fast (Lin & Murphy, 1997;Luhmann, Ahn, & Palmeri, 2006;Palmeri & Blalock, 2000). Other researchers (Sloman, 1996;Smith & Sloman, 1994) equate knowledge-based categorization with rule-based processing, which they consider as time and effort demanding and contrast it with similarity-based categorization, which they consider automatic.…”
Section: Logic Of the Current Investigationmentioning
confidence: 99%
“…Una vez que se posee el concepto, este afecta el procesamiento cognitivo (Bower, Clark, Lesgold & Winzenz, 1969;Lin & Murphy, 1997). En algunos casos el concepto puede hacer el procesamiento más eficiente.…”
Section: Los Estereotipos De Género Como Conceptosunclassified
“…Theorists have also explored the possibility that the descriptions given to concept members do not only in¯uence, but are also in¯uenced by, the learned concepts. Several empirical results and theoretical treatments lead to the suggestion that the relation between perceptual descriptions and concept representations is not unidirectional, but rather is bi-directional and mutually supporting Goldstone, Steyvers, Spencer-Smith, & Kersten, 2000;Lin & Murphy, 1997;Schyns, Goldstone, & Thibaut, 1998;Schyns & Murphy, 1994;Schyns & Rodet, 1997;Wisniewski & Medin, 1994).…”
Section: Introductionmentioning
confidence: 99%